Caring Dads intervention for fathers who have perpetrated abuse within their families: Quasi-experimental evaluation of child protection outcomes over two years. (October 2021) - Scott, Katreena; Dubov, Violeta; Devine, Christine; Colquhoun, Chrystal; Hoffelner, Carrie; Niki, Izumi; Webb, Sarah; Goodman, Deborah
Abstract: Background: In Canada, two of the most common forms of maltreatment substantiated by child protective services are child exposure to domestic violence and child physical abuse. Fathers are identified as the parent responsible for a substantial proportion of this maltreatment. Objective: This study examined whether providing a group-based intervention program for fathers was associated with greater engagement of fathers in child protection case management and with lower rates of subsequent father-perpetrated abuse. Participants: A quasi-experimental design compared child protection outcomes in families in which fathers were referred to an intervention program (Caring Dads) and either completed the group ( n = 85) or remained on a waitlist for future service ( n = 100). Methods: Data were collected from a retrospective review of administrative files over two years, starting from the time of referral to Caring Dads. Results: Initial comparisons found no significant differences in intervention and comparison group fathers in demographic characteristics, child protection concerns, and all but one area of risk and needs. Completing intervention, as compared to being waitlisted, was associated with a greater number of contacts between child protection workers and fathers over two years ( M = 30.3 vs. M = 16.7), a difference that was significant and large in size ( d = 0.81) and with lower rates of verified re-referral due to fathers' maltreatment (20.5% vs. 36.0%), a difference that was significant and between small and medium in size ( V = 0.17). Conclusions: Current results suggest that there may be significant benefits of involving fathers in child protection-linked intervention. Highlights: Child exposure to domestic violence is a commonly substantiated form of maltreatment. Fathers perpetrate a majority of child exposure to domestic violence. Over 2 yrs child protection had more contact with fathers who completed intervention. Rates of substantiated re-referral were lower for fathers who completed intervention.